Extraction and Identification of Volatile Compounds from Ocimum gratissimum Using Gas Chromatography - Usman , Md. Rageeb Md.; Vadnere, Gautam P.; Jain, Shreya C.; Patil, Divya; Patil, Prajakta (Journal of Drug Delivery and Therapeutics, 2025)
Ocimum gratissimum is a well-known aromatic plant extensively utilized in traditional medicine due to its wide range of therapeutic effects, which are attributed to its complex phytochemical composition. This research aims to extract bioactive constituents from the leaves of Ocimum gratissimum and identify them using Gas Chromatography (GC). The plant material underwent drying, powdering, and ethanolic extraction. The concentrated extract was then analyzed using GC to detect both volatile and semi-volatile compounds. The chromatographic analysis identified several significant constituents, including eugenol, thymol, and other terpenoids, which are associated with antimicrobial, anti-inflammatory, and antioxidant activities. These results highlight the phytochemical richness of Ocimum gratissimum and establish the utility of GC as an analytical tool for evaluating herbal extracts. The study supports the traditional medicinal use of the plant and opens avenues for further pharmacological exploration. Keywords: Ocimum gratissimum, Gas Chromatography, Herbal Extraction, Phytochemicals, Eugenol, Medicinal Herbs, Volatile Compounds.